Shari’ah Perspectives on Cryptocurrency Contracts: Blockchain Transactions in Light of Lubab al-Tafsir and Contemporary Islamic Economic Thought - Pranata, Imam Sufardi; Finaldy, Auli Robby; Musafa’ah, Suqiyah (JURNAL AT-TURAS, 2025)
The rapid expansion of cryptocurrency as a digital financial instrument raises critical concerns about the validity of contracts and their alignment with Shari’ah principles, particularly regarding price volatility and the absence of comprehensive regulatory frameworks. While cryptocurrency transactions promise substantial returns, they also entail considerable risks due to speculative behavior and market instability. This study examines the validity of such contracts and the practice of cryptocurrency transactions in light of classical Qur’anic exegesis and contemporary Islamic economic thought. Employing a qualitative hermeneutic analysis of Lubab al-Tafsir min Ibn Katsir combined with thematic comparison to contemporary Islamic economic models, this research explores the contractual principles of honesty, justice, legal certainty, documentation, and mutual consent in regulating cryptocurrency practices. The novelty of this study lies in constructing a framework for Shari’ah-compliant digital contracts, integrating classical tafsir insights with the challenges of blockchain-based finance. The findings reveal that although blockchain technology enhances transparency and security, persistent challenges such as volatility and regulatory ambiguity require urgent Shari’ah-based governance. This study contributes to Islamic economic jurisprudence by offering a novel evaluative framework with practical implications for policymakers, regulators, and Islamic financial institutions, ensuring that innovation in financial technology remains ethically grounded and Shari’ah-compliant.